The chloroplast genome sequence of the ornamental plant Petunia hybrida. Issue 1 (2nd January 2019) - Wong, Jerry; Mudd, Elisabeth A.; Hayes, Andrew; Day, Anil
Abstract: Petunia hybrida is a popular ornamental plant and a model for chloroplast research. A complete P. hybrida chloroplast genome sequence would advance phylogenetic studies in the Solanaceae sub-family Petunioideae and is essential for developing synthetic biology tools to study and manipulate chloroplast function for fundamental and industrial applications. Here we present the 156, 575 bp P. hybrida chloroplast genome sequence. It is comprised of 87, 083 bp large single copy and 18, 630 bp small single copy regions separated by 25, 431 bp inverted repeats. Seventy-nine proteins, 30 transfer-RNAs and four ribosomal RNA species are encoded by 113 unique genes. The results of phylogenetic analysis using complete Solanaceous chloroplast genomes are consistent with other data that supports an early split for the P. hybrida lineage away from the branch giving rise to groups containing major crops such as tobacco ( Nicotianoideae ) and potato ( Solanoideae ).